ANALISIS PENGENDALIAN MUTUCPO (Crude Palm Oil) MENGGUNAKAN SIX SIGMA DI PABRIK PENGOLAHAN CPOPT. GUNAJAYA KARYA GUMILANG KECAMATAN KENDAWANGAN KABUPATEN KETAPANG - PRAWIRO, IRIANTO SASTRO; KUSRINI, NOVIRA; NURLIZA, NURLIZA (Jurnal Social Economic of Agriculture, 2016)
The purpose of this research is to identify the quality of CPO in the palm oil Factory at PT Bumitama Gunajaya Agro. The analysis was carried out by processing the data of free faty acid, water level, and impurity level. Descriptive analysis was applied in this reaserch by using six sigma the use of six sigma aimed to identify if the quality which was produces by the  company has relied on the standard wanted by the consumer.The result reported that the quality of free faty acid remained at level of 1,3 sigma with DPMO value 317500 products that were underqualified as decided by SNI. The improvement that can be applied as in fish bone  diagram was to the human resources, the propellents, and the machines. The analysis result at water quality sigma level has been at level 3 of sigma but with DPMO value by 2700hence, having analysed by Fish Bone Diagram, machinery was the factor that sould be improve in order to improve the sigma level. Meanwhile, impurity content has approximentely reached level 4 sigma, in this case reaching the company’s target that expect the CPO quality above 3 level sigma. Therefore, at impurity content, it was unnecessary to find the problem  about the quality inapporiateness with the consumer’s standart (SNI).